Propósito negocial como limitador do planejamento tributário à luz da jurisprudência do CARF - Aranha, Fernanda Maciel de Souza (2022)
This study aims to examine how the business purpose theory has been applied as an element of validity in tax planning in Brazil, throughout the analysis of the Tax of Appeeals Council’s (“Conselho Administrativo de Recursos Fiscais – CARF”) decisions. The reason of this research is that the deficit of a specific law that rules the subject invokes legal insecurity and threatens the principle of legality, since the Council interpretation relys on notable subjectivism. For this, both deductive and inductive approach methods were used, whereas the study will, at first, fix its attention at general concepts of tax planning and, ultimately, at specific law cases and the most common criteria addressed by the Counselors